Music Therapy Reduces Pain In Labor - Nining Sulistyowati (Sean Institute, 2023)
Labor and birth are normal physiological processes. Labor pain is a physiological condition. Pain that occurs can affect the mother's condition in the form of fatigue, fear, worry and cause stress. then an effort is needed to reduce pain in laboring mothers, one of which is Music Therapy. Music therapy can be done by laboring mothers. Music therapy is useful in laboring mothers in reducing labor pain. This study aims to determine the effect of classical music therapy on labor pain in the first stage. This type of research is quantitative research with quasy experimental Designs with One Group Pretest Posttest design. The population in this study were all 30 laboring mothers. Sample technique using total sampling. With a sample of 30 respondents. The research was conducted from March to April 2023. Data analysis used wilcoxon test. The results of the study obtained the pain intensity of respondents before the intervention was averaged 3.20 with a standard deviation of 0.610. While the average pain intensity of respondents after the intervention was 2.47 with a standard deviation of 0.507. From the statistical test, it can be concluded that there is a significant effect between pain intensity before intervention and after intervention (p value = 0.000 <0.05). From the results of this study, it is known that music therapy is effective in reducing the intensity of pain in labor phase I.